Condições e contradições da atividade artística: um estudo sobre os profissionais da música e seus representantes coletivos no Brasil e em Portugal - Crocco, Fábio Luiz Tezini [UNESP] (2014)
This study aims to discuss the conditions and contradictions of the activity of professional musicians in contemporary capitalist society. The research is based on the dialogue of the collective representatives of musicians from Brazil and Portugal and seeks to reflect the extent to which their representative agencies express advocacy of the artwork and the rights of these professionals, as well as if their actions support the conditions for the autonomous achievement of musical artistic activity. We argue that the yearnings of musicians to get artistic recognition and to be able to feed themselves and their family are permeated with contradictions, as their search for artistic and professional autonomy is often hindered by the need for survival in an informal and competitive labor market, with no practical rules and job security. Musical artistic profession coexists with flexible, exploratory and poor labor relations both in the production of recorded music through phonogram producers and their intermediates, as in the execution of live music through music agents or by direct link with the employer. Therefore, in order to promote a productive research for social sciences we aim to analyze the particularities of artistic musical activity mediating socioeconomic, political and labor elements of present society.